Immunosenescence in Testicular Cancer Survivors: Potential Implications of Cancer Therapies and Psychological Distress - De Padova, Silvia; Urbini, Milena; Schepisi, Giuseppe; Virga, Alessandra; Meggiolaro, Elena; Rossi, Lorena; Fabbri, Francesco; Bertelli, Tatiana; Ulivi, Paola; Ruffilli, Federica; Casadei, Chiara; Gurioli, Giorgia; et al. (Frontiers in Oncology, 2021)
Testicular cancer (TC) is the most frequent solid tumor diagnosed in young adult males. Although it is a curable tumor, it is frequently associated with considerable short-term and long-term morbidity. Both biological and psychological stress experienced during cancer therapy may be responsible for stimulating molecular processes that induce premature aging and deterioration of immune system (immunosenescence) in TC survivors, leading to an increased susceptibility to infections, cancer, and autoimmune diseases. Immunosenescence is a remodeling of immune cell populations with inversion of the CD4:CD8 ratio, accumulation of highly differentiated memory cells, shrinkage of telomeres, shift of T-cell response to Th2 type, and release of pro-inflammatory signals. TC survivors exposed to chemotherapy show features of immunological aging, including an increase in memory T-cells (CD4+ and CD8+) and high expression of the senescence biomarker p16INK4a in CD3+ lymphocytes. However, the plethora of factors involved in the premature aging of TC survivors make the situation more complex if we also take into account the psychological stress and hormonal changes experienced by patients, as well as the high-dose chemotherapy and hematopoietic stem cell transplantation that some individuals may be required to undergo. The relatively young age and the long life expectancy of TC patients bear witness to the importance of improving quality of life and of alleviating long-term side-effects of cancer treatments. Within this context, the present review takes an in-depth look at the molecular mechanisms of immunosenescence, describing experimental evidence of cancer survivor aging and highlighting the interconnected relationship between the many factors modulating the aging of the immune system of TC survivors.